2008
DOI: 10.1590/s0100-29452008000400018
|View full text |Cite
|
Sign up to set email alerts
|

Características físicas de frutos e amêndoas e características químico-nutricionais de amêndoas de acessos de sapucaia

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a variabilidade fenotípica entre acessos de sapucaia para características físicas de frutos e amêndoas e características químico-nutricionais de amêndoas, para fins de uso em futuros trabalhos de melhoramento genético. Os frutos foram colhidos no estádio de pré-maturação e mantidos em temperatura ambiente por cerca de uma semana para completar a maturação. As seguintes características físicas e químico-nutricionais foram analisadas: peso médio de fruto, diâmetro lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
4
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 7 publications
(13 reference statements)
1
9
4
5
Order By: Relevance
“…However, with 56% genetic similarity it is possible to define several subgroups, showing that there is high genetic differentiation within the populations. Some groupings observed in this study are consistent with those reported in a study of phenotypic characteristics that used the same AGB as used here (Souza et al, 2008). In that study, four groups were formed and there was phenotypic variability among the accessions of sapucaia for most of the characteristics analyzed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, with 56% genetic similarity it is possible to define several subgroups, showing that there is high genetic differentiation within the populations. Some groupings observed in this study are consistent with those reported in a study of phenotypic characteristics that used the same AGB as used here (Souza et al, 2008). In that study, four groups were formed and there was phenotypic variability among the accessions of sapucaia for most of the characteristics analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…This chestnut tree originates from the Amazon and is distributed widely throughout Brazil. Its nuts are an important source of calories (average: 736.87 kcal/100 g), are rich in calcium, phosphorus, and manganese, and can be consumed by humans and animals as a source of lipids and proteins (Souza et al, 2008). Several parts of the plant have been used in popular medicine, and recent studies have revealed the presence of compounds that have moderate cytotoxic activity (Silva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em comparação com outros tipos de castanha, os resultados obtidos neste estudo mostram que a castanha-do-gurgueia é uma boa fonte de P, K, Mg, PB, FB, CT e E. Por exemplo, em PB, é superior ao teor obtido por Crepaldi et al (2001) TAKEMOTO et al, 2001;CARVALHO, 2005;SOUZA et al, 2008).…”
Section: Resultsunclassified
“…No geral as amêndoas são ricas em proteínas, lipídios e fibras, possuem tiamina, riboflavina, niacina e vitaminas B1 e B2, além de teores consideráveis de fósforo, potássio, cálcio e magnésio, são pobres em sódio e não possuem colesterol (SOUZA et al, 2008). A castanheira (Bertholletia excelsa Humb.…”
Section: Introductionunclassified